Role of cytokines, IL1-β and IL-10, in the development of endocrine ophthalmopathy in Graves’ disease (Ukrainian Journal of Ophthalmology, 2025)
Background: Endocrine ophthalmopathy (EO) is a disease which is characterized by progressive autoimmune inflammation of extraocular muscles and retrobulbar adipose tissue, and is accompanied by infiltration, edema and proliferation of retrobulbar adipose tissue, muscles and connective tissue, leading to worsened quality of life, limited capacity for work and even ocular atrophy. It has been demonstrated that cytokines are involved in the development of autoimmune ophthalmopathy in Graves’ disease (GD). Thus, the secretion of IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, and TNFα were increased several dozenfold in active ophthalmopathy, but the specificity of cytokines in EO is still a subject of discussion among researchers.Purpose: To assess the levels of proinflammtory cytokines (IL-1β) and anti-inflammatory cytokines (IL-10) in Graves’ disease complicated by endocrine ophthalmopathy.Material and Methods: Forty-three patients with Graves’ disease (33 women and 10 men; age, 18 to 71 years) underwent an examination. They were divided into two groups based on the presence or absence of EO: GD plus EO (24 patients) and GD only (19 patients). Disease duration was 2.2±0.4 years for patients with GD plus EO versus 3.98±0.74 years for patients with GD only (р 0.05).
Keywords: Graves’ disease; endocrine ophthalmopathy; IL-1β; IL-10